Two Cases of Mycobacterium microti-Derived Tuberculosis in HIV-Negative Immunocompetent Patients - Stefan Niemann; Elvira Richter; Helga Dalügge-Tamm; Hejko Schlesinger; Dietrich Graupner; Bodo Königstein; Gudrun Gurath; Ulf Greinert; Sabine Rüsch-Gerdes (Emerging Infectious Diseases, 2000)
We describe two cases of Mycobacterium microti infection causing pulmonary tuberculosis (TB) in HIV-seronegative immunocompetent patients in Germany. The isolates were identified as M. microti of the llama and vole types, according to spoligotype patterns. Our data demonstrate that M. microti can cause severe pulmonary TB in immunocompetent patients.